2014
DOI: 10.2147/ceg.s73067
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease in children: is it a problem in Kuwait?

Abstract: BackgroundCeliac disease (CD) is a chronic inflammatory disease of the small intestine triggered by gluten ingestion. The objective of this study is to describe our experience with CD children in Kuwait.MethodsThe records of children with CD seen in the pediatric gastroenterology unit between February 1998 and December 2010 were retrospectively reviewed. Patients were referred because of symptoms or positive CD antibody screening of a high-risk group (type 1 diabetes and Down syndrome).ResultsForty-seven patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 20 publications
2
25
2
Order By: Relevance
“…Moreover, a study from United Kingdom reported that the prevalence of CD among children older than two years had tripled over the 20 years between 1993 and 2012 13) . Similar to our study, most of the patients with CD from Kuwait were diagnosed in the second half of the study period (between 1998 and 2010) 14) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, a study from United Kingdom reported that the prevalence of CD among children older than two years had tripled over the 20 years between 1993 and 2012 13) . Similar to our study, most of the patients with CD from Kuwait were diagnosed in the second half of the study period (between 1998 and 2010) 14) .…”
Section: Discussionsupporting
confidence: 89%
“…This incidence is also low when compared to studies from Italy and United Kingdom which reported incidence of 11.9 and 11.8 per 100 000 person-years; respectively 12,13) . This variation in the prevalence and incidence of CD between different countries can be attributed to vague presentations and delayed diagnosis in one hand; and to increased number of screened high risk groups and/or increased awareness among physicians about CD on the other hand 6,14,29,30) . CD tends to manifest more in children aged 0-4 years 12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 While this meta-analysis has confirmed that CD is more common in women in Asia too as compared with that in men, the ratio of women to men was only 1.25, which is much lower than that observed in the Caucasian population where male-to-female ratio varies between 1:2-3. 55,56 The reason for the much lower difference in the prevalence in women and men in Asia could be secondary to inclusion of lesser number of women in the studies mentioned previously (total men, 13 067, and total women, 7502).…”
Section: Discussionmentioning
confidence: 96%
“…The discrimination ability of each proposed prognostic score was assessed by both the C-index and the Sommer"s D [21]. To adjust for overfitting, our results were internally validated with bootstrapping [22,23].…”
Section: Discussionmentioning
confidence: 99%